An AN ANALYSIS OF EMERGENCY RESPONSE COSTS DUE TO FALSE ALARM SYSTEM - Isrorudin Isrorudin; Agus Maulana; Asep Maryono; Fergyanto E. Gunawan; Muhammad Asrol (JARES (Journal of Academic Research and Sciences), 2022)
Losses from fire events can be minimized if the fire detection and alarm system installed in an area function properly. The conditions will be different if an alarm that sounds is not the result of real conditions that can trigger a fire - also known as a false alarm. The false alarm condition gives a loss to the company. In this research, an analysis and comparison of costs in the detection and alarm systems conducted on the existing company fires with the same risk of false alarms, repairs fire detection and alarm system, and investment costs. The probability of a false alarm calculated in the existing condition, to know the potential losses charged to the company due to unnecessary emergency response activities. As well, investment costs were analysed to improve the performance of the system. Two alternative conditions were found to improve company’s performance.